M16 Their point of view: patient experience of a dgh pleural service. (15th November 2017) - Conroy, K; Fretwell, T; Tedd, H; Killen, J
Abstract : Pleural disease constitutes a significant part of the workload on the respiratory unit but little information is recorded of the patient experience. We sought to record the experiences of our patients and look for ways to improve upon them. Method: We provided a brief questionnaire to in-patients and day attenders using our pleural service and recorded breathlessness, pain and anxiety on a visual analogue scale. A follow up questionnaire was collected within two weeks to record post procedure dyspnoea and time to improvement. We recorded pre-procedure questionnaires in 29 patients and 24 pre and post procedure in total from patients undergoing a mixture of procedures. Twelve had intercostal chest drains, eleven underwent therapeutic aspiration and six had diagnostic aspiration. Results: We found that patients undergoing intercostal drain insertion reported the greatest improvement in dyspnoea on visual analogue scale(65.8% reduction), compared with 38% reduction in patients undergoing therapeutic aspiration. Excluding the diagnostic aspiration cohort, 85% of patients reported an improvement of their breathlessness over minutes or hours. Pain scores were similar between the therapeutic aspiration and chest drain group with 45% and 50% of patients reporting moderate to severe pain. We found the therapeutic aspiration group tended to report greater pre-procedure anxiety than the chest drain group. 63% of patients in the therapeutic aspiration cohort reported moderate or severe pre-procedure anxiety, compared with only moderate or minor anxiety reported in the chest drain group. Fear of pain was particularly common in the therapeutic aspiration group. All patients reported feeling adequately prepared for the procedure. Despite this, when later asked how we could improve their experience four patients felt they would have liked more information about their procedure. Conclusion: Our study demonstrates that chest drain insertion is superior for dyspnoea relief and causes similar discomfort levels to therapeutic aspiration. Anxiety is common, but worse in the therapeutic aspiration group. A desire for more information on pleural procedures was identified. Outcome: We have introduced a patient information leaflet and have reviewed our anaesthetic and analgesia practice, and plan to repeat our questionnaire.